A gate to the world for all? The reaction of neighborhoods in Hamburg to refugee housings - Marek Endrich (University of Hamburg, Institute of Law and Economics (ILE), 2022)
This paper analyses the political reaction of residents to refugee housings in their neighborhood. The city of Hamburg, Germany, experienced between 2014 and 2021 large refugee inflows that required many new housings. Openings of refugee housings led to an increase in the vote share of anti-immigrant right-wing parties in the neighborhood. The effect is persistent, driven by the exposure of residents to large reception centers and followup accommodations and amplified for facilities with a high share of male inhabitants. Results are robust to a matching estimator that accounts for an unbalanced distribution of housings. Neighborhoods with worse economic conditions, many migrants of other origins and a relatively large share of allocated refugee housings react more negatively to openings. With the finding that new housings come with electoral losses for the ruling party, it suggests that frustration by residents about a biased allocation is one contributing factor to the vote gains of right-wing parties.
Keywords: F22; D72; J15; H76; 330; migration; political economy; refugee housing; voting